Dopaminergic Pathway Genes Influence Adverse Events Related to Dopaminergic Treatment in Parkinson's Disease - Sara Redenšek; Dušan Flisar; Maja Kojović; Milica Gregorič Kramberger; Dejan Georgiev; Zvezdan Pirtošek; Maja Trošt; Vita Dolžan (Frontiers Media S.A., 2019)
Dopaminergic pathway is the most disrupted pathway in the pathogenesis of Parkinson's disease. Several studies reported associations of dopaminergic genes with the occurrence of adverse events of dopaminergic treatment. However, none of these studies adopted a pathway based approach. The aim of this study was to comprehensively evaluate the influence of selected single nucleotide polymorphisms of key dopaminergic pathway genes on the occurrence of motor and non-motor adverse events of dopaminergic treatment in Parkinson's disease. In total, 231 Parkinson's disease patients were enrolled. Demographic and clinical data were collected. Genotyping was performed for 16 single nucleotide polymorphisms from key dopaminergic pathway genes. Logistic and Cox regression analyses were used for evaluation. Results were adjusted for significant clinical data. We observed that carriers of at least one COMT rs165815 C allele had lower odds for developing visual hallucinations (OR = 0.34; 95% CI = 0.16-0.72; p = 0.004), while carriers of at least one DRD3 rs6280 C allele and CC homozygotes had higher odds for this adverse event (OR = 1.88; 95% CI = 1.00-3.54; p = 0.049 and OR = 3.31; 95% CI = 1.37-8.03; p = 0.008, respectively). Carriers of at least one DDC rs921451 C allele and CT heterozygotes had higher odds for orthostatic hypotension (OR = 1.86; 95% CI = 1.07-3.23; p = 0.028 and OR = 2.30; 95% CI = 1.26-4.20; p = 0.007, respectively). Heterozygotes for DDC rs3837091 and SLC22A1 rs628031 AA carriers also had higher odds for orthostatic hypotension (OR = 1.94; 95% CI = 1.07-3.51; p = 0.028 and OR = 2.57; 95% CI = 1.11-5.95; p = 0.028, respectively). Carriers of the SLC22A1 rs628031 AA genotype had higher odds for peripheral edema and impulse control disorders (OR = 4.00; 95% CI = 1.62-9.88; p = 0.003 and OR = 3.16; 95% CI = 1.03-9.72; p = 0.045, respectively). Finally, heterozygotes for SLC22A1 rs628031 and carriers of at least one SLC22A1 rs628031 A allele had lower odds for dyskinesia (OR = 0.48; 95% CI = 0.24-0.98, p = 0.043 and OR = 0.48; 95% CI = 0.25-0.92; p = 0.027, respectively). Gene-gene interactions, more specifically DDC-COMT, SLC18A2-SV2C, and SLC18A2-SLC6A3, also significantly influenced the occurrence of some adverse events. Additionally, haplotypes of COMT and SLC6A3 were associated with the occurrence of visual hallucinations (AT vs. GC: OR = 0.34; 95% CI = 0.16-0.72; p = 0.005) and orthostatic hypotension (ATG vs. ACG: OR = 2.48; 95% CI: 1.01-6.07; p = 0.047), respectively. Pathway based approach allowed us to identify new potential candidates for predictive biomarkers of adverse events of dopaminergic treatment in Parkinson's disease, which could contribute to treatment personalization.